2016
DOI: 10.3122/jabfm.2016.04.150363
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Findings of Delayed Diagnostic Evaluation to Primary Care Providers

Abstract: Background:We previously found that an intervention involving electronic algorithms to detect delays in follow-up of cancer-related abnormal or "red-flag" findings and communicating this information to primary care providers (PCPs) led to more timely diagnostic evaluation. In this study, we examined the effectiveness of various communication strategies to inform PCPs about the delayed follow-up.Methods: After identifying follow-up delays through electronic health record-based algorithms and record reviews, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
(13 reference statements)
1
11
0
Order By: Relevance
“…Studies have demonstrated that alert systems such as electronic health record-based trigger algorithms and the use of patient navigator programs can help improve cancer screening rates and prevent prolonged diagnostic evaluation. [36][37][38][39][40][41][42] The similar odds of delivering a colonoscopy for low-income and non-white patients may be due in part to additional care coordination or patient navigation personnel that were present in all practices during the study. Previous research has shown that patient navigation can reduce disparities in colorectal cancer prevention for racial/ethnic minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that alert systems such as electronic health record-based trigger algorithms and the use of patient navigator programs can help improve cancer screening rates and prevent prolonged diagnostic evaluation. [36][37][38][39][40][41][42] The similar odds of delivering a colonoscopy for low-income and non-white patients may be due in part to additional care coordination or patient navigation personnel that were present in all practices during the study. Previous research has shown that patient navigation can reduce disparities in colorectal cancer prevention for racial/ethnic minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…13 Safety nets like the ones described in this study can provide an innovative approach by incorporating multiple, cross-cutting factors (including interdisciplinary teams), facilitating infrastructure development such as reporting tools and registries, and promoting a culture of safety. 1 , 4 , 14 18 …”
Section: Discussionmentioning
confidence: 99%
“…Physicians or other team members must take action. 36 We believe future efforts are needed to use triggers prospectively in real-time clinical settings, as well as to explore more advanced algorithms that attempt to glean information from freetext notes in the record. …”
Section: Discussionmentioning
confidence: 99%